Analisis Break-Even Point (BEP) UMKM Bakso Goreng A.M. di Kabupaten Ketapang - Kiki Amelia; Irfan Cholid; Assrorudin Assrorudin; Ayu Dian Pratiwi Permatahati; Rois Indriawan (Journal of Applied Accounting, 2026)
This study aims to analyze the financial feasibility of A.M. fried meatballs MSMEs in Ketapang Regency. This study uses a qualitative descriptive method with direct observation techniques and interviews with business actors. The results of the study indicate that the total operational costs of the business are Rp38,047,000 per month, consisting of fixed costs of Rp 4.050.000 and variable costs of 23.974.000. The production volume reaches 7,200 pcs with a selling price of Rp10,000 per pc, resulting in a total revenue of Rp72,000,000 per month. The cost of production is Rp 5.284,30 per pc with a profit per pc of Rp4.715,70. The BEP value is 607 pcs per day or  pcs 18.210 per month, while the B/C Ratio is 1.87. Based on these results, the A.M. Fried Meatballs business is considered feasible to run and develop. Keywords: MSME, fried meatballs, break-even analysis, operating expense, contribution margin, margin of safety.